Novel transcription regulatory elements in Caenorhabditis elegans muscle genes - GuhaThakurta, Debraj (Cold Spring Harbor Laboratory Press, 2004)
We report the identification of three new transcription regulatory elements that are associated with muscle gene expression in the nematode Caenorhabditis elegans. Starting from a subset of well-characterized nematode muscle genes, we identified conserved DNA motifs in the promoter regions using computational DNA pattern-recognition algorithms. These were considered to be putative muscle transcription regulatory motifs. Using the green-fluorescent protein (GFP) as a reporter, experiments were done to determine the biological activity of these motifs in driving muscle gene expression. Prediction accuracy of muscle expression based on the presence of these three motifs was encouraging; nine of 10 previously uncharacterized genes that were predicted to have muscle expression were shown to be expressed either specifically or selectively in the muscle tissues, whereas only one of the nine that scored low for these motifs expressed in muscle. Knockouts of putative regulatory elements in the promoter of the mlc-2 and unc-89 genes show that they significantly contribute to muscle expression and act in a synergistic manner. We find that these DNA motifs are also present in the muscle promoters of C. briggsae, indicating that they are functionally conserved in the nematodes.